Clustering of excess health concerns for electromagnetic fields among health personnel: A quantitative and qualitative approach. (August 2015) - Gerakopoulou, Patricia; Matsoukis, Ioannis L; Giagkou, Nick; Dessypris, Nick; Cassimos, Dimitrios C; ,; Petridou, Eleni Th
Clustering patterns, among health-care personnel, of excessive concerns pertaining to perceived electromagnetic field–related health impacts, as contrasted to those from other environmental factors, were explored. Knowledge/excessive concerns of 722 health-care personnel were assessed using a 22-item structured questionnaire along with a double-phase qualitative study comprising semistructured interviews and focus groups. Over 75 percent of the participants had high perceived knowledge, whereas accuracy was limited to <20 percent and correctness to 8 percent. An "excessive concern" group was clearly distinguished from a "relaxed attitude" one. Clustering of excessive concerns may derive from personal beliefs, suggesting a risk governance issue for health education policies.